Deposition mechanism and photodetector application of plasma-enhanced atomic layer-deposited Ta2O5 films at various deposition temperatures - Wang, Chen; Zhou, Chen-Hao; Wang, Jian-Gui; Cho, Yun-Shao; Wu, Wan-Yu; Wuu, Dong-Sing; Huang, Chien-Jung; Lien, Shui-Yang (Ceramics international, 2025)
In this work, a plasma-enhanced atomic layer deposition (PEALD) has been employed to fabricate Ta2O5 thin films for application in ultraviolet detection. The film properties have been explored in a wide deposition temperature range of 200–450 °C. A deposition mechanism with three deposited states of physisorption, chemisorption and desorption has been proposed to illustrate the temperature-controlled properties of Ta2O5 films. The ALD temperature window has been decided to be 250−350 °C with a close growth per cycle of ∼0.61 Å/cycle and the chemisorption is dominant in this temperature range. Based on those Ta2O5 films deposited in ALD window, Ta2O5/p-Si heterojunction ultraviolet photodetectors have been fabricated, which can achieve a superior performance with a high photo/dark current ratio of 7.2 × 104, a high responsivity of 0.61 A/W and a good specific detectivity of 1.9 × 1012 Jones at −5 V and 254 nm ultraviolet light. In addition, photodetectors with Ta2O5 films deposited at 350 °C shows an improved spectral response in the wavelength range from 200 nm to 360 nm with a peak response of 0.82 A/W at 296 nm.